Sisu(datu), the Funny Female Dragon of the Disney Universe - Tóth, Zsófia Anna (AMERICANA E-journal of American Studies in Hungary, 2023)
In the Disney movie Raya and the Last Dragon (2021, hence mentioned as Raya) Sisu(datu) or simply just Sisu, the dragon, is a unique character, as she represents a merger of both the West and the East, constituting a bridge and playing a major role in cultural diplomacy while she is one of the first female Disney characters actively producing humor. The paper reveals what critics have so far thought about humor in Disney in general by highlighting that even if Sisu is not the first positive dragon character in a Western animated film, she stands out as a complex figure. She is sacred with her dragon abilities and magical status while also being sacrilegious with her use of humor and occasional clumsiness at the same time. At the height of the tension between the USA and China (due to the COVID-19 pandemic), this character appeared as a regenerative gesture of cultural diplomacy and a positive point of reference for Asian Americans especially, since Sisu was voiced by Awkwafina. In sum, the paper examines the use of humor in this animated film from various points of view taking account of Asian American identities, Asian and American cultural differences as well as the questions of women’s humor and that of how the Disney Company is currently rethinking its humor strategies.